Evaluasi Pemberian Air Irigasi Saluran Sekunder Srengseng Hilir dari Bendung Tetap Cikarang Bekasi Laut - Bahri, Fahmi Fathul; Yulius, Elma; Srie Gunarti, Anita Setyowati (Universitas Islam 45, 2019)
Cikarang Bekasi Laut (CBL) is a fixed-dam river-flow that flows through the building for upstream srengseng channel. Srengseng Hilir Secondary-Channel has 32 buildings for watering the rice fields in the Sukatani sub-district. The problem happened in the distribution of water when there is a loss of irrigation water due to infiltration of water into the soil where the soil is saturated. This causes a shortage of debit for field irrigation due to water loss in the secondary channel. The method used in Water Supply Evaluation of Irrigation Cikarang Bekasi Laut (CBL) for the Secondary Channel Srengseng Hilir D.I. Jatiluhur are the maximum discharge data, minimum discharge, and average discharge of the Fixed Cikarang Bekasi Laut (CBL) Dam in 5 year-period and calculating water requirements and water availability in D.I. Jatiluhur. Result showed that the P1 channel has an irrigation area of 105 ha and a channel length of 1906 m with an actual discharge of 2714 liters/sec and has irrigation efficiency of 5.71%. Channel P2 has an irrigation area of 106 ha and channel length of 1006 m with actual discharge of 1560 liters/sec and has irrigation efficiency of 6.11%. P3 channel has an irrigation area of 137 ha and 894 m channel length with an actual discharge of 175 liters/second and has irrigation efficiency of8.41%. Channel P4 has an irrigation area of 50 ha and a channel length of 951 m with an actualdischarge of 180 liters/second and has irrigation efficiency of 21.10%. Channel P5 has an irrigationarea of 71 ha and a channel length of 835 m with an actual discharge of 274 litters/sec and has irrigationefficiency of 37.97%. Channel P6 has an irrigation area of 74 ha and a channel length of 775 m with anactual discharge of 411 liters/sec and has irrigation efficiency of 63.79%.